Unfreedom of the press - Levin, Mark R. (Mark Reed), 1957- (New York, Threshold Editions, 2019)
Fox News host Mark Levin shows how those entrusted with news reporting today are destroying freedom of the press from within: "not government oppression or suppression," he writes, but self-censorship, group-think, bias by omission, and passing off opinion, propaganda, pseudo-events, and outright lies as news. Levin takes the reader on a journey through the early American patriot press, which proudly promoted the principles set forth in the Declaration of Independence and the Constitution, followed by the early decades of the Republic during which newspapers around the young country were open and transparent about their fierce allegiance to one political party or the other. It was only at the start of the Progressive Era and the twentieth century that the idea of "objectivity of the press" first surfaced, leaving us where we are today: with a partisan party-press overwhelmingly aligned with a political ideology but hypocritically engaged in a massive untruth as to its real nature.
News as political and ideological activism -- The early patriot press -- The modern democratic party-press -- The real threat to press freedom -- News, propaganda, and pseudo-events -- The New York times betrays millions -- The truth about collusion, abuse of power, and character -- Epilogue: A standardless profession.
Includes bibliographical references (pages 231-258).
Keywords: Journalism -- Political aspects -- United States -- History; Freedom of the press -- United States -- History; Press and politics -- United States -- History; Journalism -- Objectivity -- United States -- History; History